A race to the bottom in labour standards? An empirical investigation - Ronald B. Davies; Krishna Chaitanya Vadlamannati (University College Dublin, UCD School of Economics, 2011)
Among the many concerns over globalization is that as nations compete for mobile firms, they will relax labour standards as a method of lowering costs and attracting investment. Using spatial estimation on panel data for 148 developing countries over 18 years, we find that the labour standards in one country are positively correlated with the labour standards elsewhere (i.e. a cut in labour standards in other countries reduces labour standards in the country in question). This interdependence is more evident in labour practices (i.e. enforcement) than in labour laws. Further, competition is most fierce in those countries with already low standards.
Keywords: J83; F23; O19; 330; Labour Standards; Competition for FDI; Spatial Econometrics